DESIGN OF ISLAMIC PSYCHOPEDAGOGY MODEL ‎FOR ‎EMOTIONAL AND MORAL DEVELOPMENT OF ‎STUDENTS IN ‎HIGHER EDUCATION - Nofitri, Abelia; Andini, Betti; Gusmaneli (International Journal of Multidisciplinary Reseach, 2025)
Students in contemporary higher education face increasing emotional stress and ‎spiritual challenges, while traditional pedagogical models largely emphasize ‎cognitive outcomes, leaving holistic development insufficiently addressed. This ‎study investigates the potential of Islamic psychopedagogy to foster emotional ‎and spiritual well-being among university students, focusing on its theoretical ‎foundations and practical applications within higher education contexts. Using ‎a qualitative, literature-based approach, the research synthesizes insights from ‎Islamic educational thought, psychology, and modern pedagogical practices. ‎Findings reveal that Islamic psychopedagogy provides an integrative ‎framework that enhances students’ emotional resilience, spiritual awareness, ‎and ethical responsibility. By embedding these principles into curriculum ‎design, teaching strategies, and student-centered learning environments, this ‎approach supports the development of holistic learners who are morally ‎grounded, emotionally balanced, and academically competent. The study ‎highlights Islamic psychopedagogy as a culturally relevant and transformative ‎paradigm, offering valuable guidance for inclusive, value-based, and well-being-‎centered higher education. ‎